Proposed Changed to WTO Special and Differential Treatment Provisions: An Analysis from the Perspective of Asian LDCs - Mustafizur Rahman; Kazi Mahmudur Rahman (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2006)
Special and differential treatment (S&D) provisions introduced in the GATT and the WTO in support of strengthened global integration of the developing country (DC) and least developed country (LDC) members have come under increasing scrutiny and criticism in recent years. One criticism has been that most of the S&D provisions are weak in their formulations, i.e., are expressed in the form of best endeavour clauses and hence are non-enforceable. The other strand of argument is that that in order for the S&D provisions to be effective and enforceable they ought to be targeted to countries that are in need of them most and be applied not in general, but with discretion, by identifying and targeting select group of developing countries that require a particular type of support most.
Keywords: F1; 330; Special and differential treatment; GATT